Between Mandates and Molding Minds: The Challenge of Teacher Autonomy Today - Joshua Cole Hill-Cloyd; Cynthia L Miller (Undergraduate Research Journal for the Human Sciences, 2023)
In recent years, Texas schools have witnessed a significant decline in teacher autonomy, attributable primarily to three factors: an increased emphasis on standardized testing, the prevalence of top-down leadership and bureaucracy, and the adoption of third-party curricula and commercialized content. These elements have collectively constrained educators' ability to adapt and innovate according to the unique needs of their students. Additionally, this issue has had profound ripple effects on families and communities in several ways. Possible solutions for increasing teacher autonomy will be provided that offer multiple benefits to the education system, teachers, students, and the broader community.
Keywords: teacher autonomy; standardized testing; top down leadership; third-party curricula